DIGITAL MARKETING ADOPTION BY MSMES IN INDONESIA: BETWEEN TECHNOLOGICAL AWARENESS AND RESOURCE LIMITATIONS - Rakesh Sitepu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This research delves into the burgeoning landscape of digital marketing adoption among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. While technological awareness of digital marketing's potential benefits is growing, significant resource limitations often hinder widespread implementation. This abstract explores the interplay between this awareness and these constraints, examining the opportunities and challenges faced by Indonesian MSMEs in leveraging digital tools for growth and competitiveness. The study investigates the key factors influencing the adoption of digital marketing strategies, including the level of digital literacy, financial resources, access to infrastructure, and perceived benefits. It also considers the types of digital marketing tools and platforms most commonly utilized by MSMEs in the Indonesian context. Furthermore, the research analyzes the impact of digital marketing adoption on various aspects of MSME performance, such as market reach, customer engagement, and sales growth. Ultimately, this research aims to provide insights into the current state of digital marketing adoption within the Indonesian MSME sector, identify the key barriers to broader uptake, and suggest potential strategies to facilitate more effective integration of digital marketing practices. By understanding these dynamics, stakeholders can develop targeted interventions to empower Indonesian MSMEs to thrive in the digital economy.